ADVANTAGEOUS OF BENEFICIAL MICROBES FOR BIOREMEDIATION OF ADULTERATED GLOBAL-CULTIVATED SOILS - Kamal Prasad (Innovare Journal of Life Sciences, 2023)
The soil is one of the most valuable resources since it forms the foundation for many important life processes and ecosystem purposes. Worldwide, soil pollution is a result of human activities that are not sustainable, such as the use of dangerous inorganic chemicals. The mining, production, transportation, end-user use, disposal, and accidental discharge of chemicals all contribute to soil contamination, which in turn jeopardizes human life, livestock, wildlife, and entire ecosystems. Purifying and decontaminating soil with conventional procedures is labor-intensive and time-consuming and can modify the soil’s physical, chemical, and biological properties. Furthermore, they do not always ensure that all impurities are eliminated. Sustainable and cutting-edge technology has developed over the last few decades. Biological soil remediation solutions, also known as soft remediation options, are being developed to integrate, namely efficient removal of soil contaminants, mitigation of soil ecotoxicity, and reduction of legally and ethically mandated hazards to the environment and human health. Soil remediation methods should not only repair soil health and provide necessary system services but also reduce noxious waste concentrations in the soil to below regulatory limits. The microorganisms have shown promise in the clean-up of soils contaminated with radioactive contaminants, heavy metals, chemical fertilizers in excess, trichlorethylene, trinitrotoluene, herbicides such as atrazine, and organophosphates. The cost of cleaning up environmental pollutants with eco-friendly technology is inexpensive when compared to other approaches, including conventional ones. The focus of the current manuscript is on using beneficial bacteria to clean up polluted farmland to ensure the longevity of the subsequent generation.